Assessment of water quality of the ex-sand mining sites in Pasir Sakti District East Lampung for tilapia (Oreochromis niloticus) culture - Qadar Hasani; Niken Tunjung Murti Pratiwi; Yusli Wardiatno; Hefni Effendi; Herman Yulianto; Maulid Wahid Yusuf; Rachmad Caesario; F Farlina (Journal of Degraded and Mining Lands Management, 2021)
Sand mining activities in Pasir Sakti District, East Lampung Regency, have changed the landscape and the allotment of land around it. The former sand mining area now becomes large puddles that are not utilized. This study aimed to analyze the suitability of water quality in ex-sand mining areas for tilapia (Oreochromis niloticus) culture. Observations were carried out at three stations in January-October 2019. Water quality measurements were performed to check water depth, clarity, temperature, current, dissolved oxygen, pH, salinity, nitrate, phosphate, iron, sulfate, and phytoplankton density. Analysis of suitability for aquaculture was carried out using weighting and scoring methods. Based on the results of the suitability analysis, the scoring result of the sand mining land for O.niloticus culture was in the range of 64% -68%. This score is classified as marginally suitable. The parameters with low scores are clarity, dissolved oxygen, temperature, pH, ammonia, phosphate, and iron (Fe) concentration parameters. Meanwhile, salinity, nitrate, sulfate, and phytoplankton density indicate conditions that are suitable for aquaculture. Therefore, severe treatment is needed to improve water quality to make it ideal for O.niloticus culture.